(untitled) (World Bulletin of Education and Learning, 2025)
The article discusses the specific features of didactic games as an effective tool for developing preschool children. It also presents the main and supplementary components of didactic games. Collectively, didactic games contribute to the formation of children’s communicative skills; the development of thinking, imagination, and creative activity; and the cultivation of cognitive interests. At an early age, play becomes a type of activity that guides personal development. Through play, the child’s personal qualities, attitudes toward reality, and interactions with people are shaped.